Attitudes and experiences of cancer patients toward the provision of audio recordings of their own medical encounter: a cross-sectional online survey - Topf, Cheyenne; Scholl, Isabelle; Hahlweg, Pola (Frontiers in Psychology, 2024)
The provision of audio recordings of their own medical encounters to patients, termed consultation recordings, has demonstrated promising benefits, particularly in addressing information needs of cancer patients. While this intervention has been explored globally, there is limited research specific to Germany. This study investigates the attitudes and experiences of cancer patients in Germany towards consultation recordings.We conducted a nationwide cross-sectional quantitative online survey, informed by semistructured interviews with cancer patients. The survey assessed participants' attitudes, experiences and desire for consultation recordings in the future. The data was analyzed using descriptive statistics and subgroup analyses.Results: A total of 287 adult cancer patients participated. An overwhelming majority (92%) expressed a (very) positive attitude. Overall, participants strongly endorsed the anticipated benefits of the intervention, such as improved recall and enhanced understanding. Some participants expressed concerns that physicians might feel pressured and could become more reserved in their interactions with the use of such recordings. While a small proportion (5%) had prior experience with audio recording medical encounters, the majority (92%) expressed interest in having consultation recordings in the future.We observed positive attitudes of cancer patients in Germany towards consultation recordings, paralleling international research findings. Despite limited experiences, participants acknowledged the potential benefits of the intervention, particularly related to recalling and comprehending information from medical encounters. Our findings suggest that the potential of the intervention is currently underutilized in German cancer care. While acknowledging the possibility of a positive bias in our results, we conclude that this study represents an initial exploration of the intervention's potential within the German cancer care context, laying the groundwork for its further evaluation.